HALAL BUSINESS TRANSFORMATION: MEETING CHALLENGES AND OPPORTUNITIES IN THE AGE OF TECHNOLOGY - Linatul Uyun (CV. Fahr Publishing, 2023)
This study aims to develop an effective digital transformation model for halal businesses in the modern era, with a focus on improving operational efficiency, customer satisfaction, and global competitiveness. The research method uses a mixed methods approach, combining a quantitative survey of 200 halal businesses in Indonesia and in-depth interviews to explore experiences and challenges in the adoption of digital technology. The results showed that 85% of respondents reported an increase in operational efficiency, 75% noted an increase in customer satisfaction, and there was an average operational cost reduction of 15%. Linear regression analysis showed a significant positive relationship between technology adoption and improved business performance. In addition, the study identified challenges such as resistance to change and limited digital literacy, and suggested solutions through training, collaboration with technology companies, and government policy support. The global usefulness of this research lies in providing a framework that can be adopted by halal businesses in different countries to improve competitiveness and economic sustainability in an increasingly competitive global market